2016
DOI: 10.3389/fbioe.2016.00054
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Dynamic Changes in Plantar Pressure Gradient in Diabetics with Peripheral Neuropathy

Abstract: Diabetic foot ulcers remain one of the most serious complications of diabetes. Peak plantar pressure (PPP) and peak pressure gradient (PPG) during walking have been shown to be associated with the development of diabetic foot ulcers. To gain further insight into the mechanical etiology of diabetic foot ulcers, examination of the pressure gradient angle (PGA) has been recently proposed. The PGA quantifies directional variation or orientation of the pressure gradient during walking and provides a measure of whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(68 citation statements)
references
References 50 publications
3
63
0
2
Order By: Relevance
“…Other work has also identified that an increase in the viscoelasticity of plantar soft tissues, especially at the first metatarsophalangeal joint may be a crucial factor for elevated peak plantar pressures in people with DPN [ 51 ]. More recent work has outlined that new measures of plantar pressure such as the pressure gradient angle which quantifies the time-varying directions of plantar pressure may provide more valuable information regarding the plantar stressors experienced by people with DPN [ 52 ]. Whether measuring the viscoelasticity of plantar tissue and pressure gradient angles in people with active DFUs provides more insight on the biomechanical mechanisms underlying delayed wound healing is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Other work has also identified that an increase in the viscoelasticity of plantar soft tissues, especially at the first metatarsophalangeal joint may be a crucial factor for elevated peak plantar pressures in people with DPN [ 51 ]. More recent work has outlined that new measures of plantar pressure such as the pressure gradient angle which quantifies the time-varying directions of plantar pressure may provide more valuable information regarding the plantar stressors experienced by people with DPN [ 52 ]. Whether measuring the viscoelasticity of plantar tissue and pressure gradient angles in people with active DFUs provides more insight on the biomechanical mechanisms underlying delayed wound healing is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…An F-scan system (Tekscan, South Boston, MA) was used to measure the plantar pressure data of the right foot in standardized shoes [ 33 ] during walking on the treadmill. Each F-scan in-shoe sensor contains 960 sensing pixels (sensels).…”
Section: Methodsmentioning
confidence: 99%
“…In-shoe pressure, unfortunately, is a difficult and expensive parameter to measure. Pressure-sensing devices are available such as the Tekscan F-scan [15], however, these are expensive, have a relatively short product life span and are not be suitable for everyday use [16].…”
Section: Devices For Diagnosismentioning
confidence: 99%